Manajemen Konflik dan Koordinasi Antar Unit Kerja di Lingkungan Dinas Pendidikan dan Kebudayaan Kabupaten Sidoarjo dalam Implementasi Program Prioritas Daerah - Widi Astuti; Widyawati Widyawati; Nihayatus Sholichah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research intends to examine conflict resolution and collaboration between units in the Department of Education and Culture of Sidoarjo Regency while carrying out regional priority programs. The research background arises from the increasing intricacy of bureaucracy and the overlapping jurisdictions among divisions, which impact the efficiency of implementing educational programs. This research utilizes a qualitative case study method, gathering data through comprehensive interviews, participatory observation, and analysis of institutional documents. Informants consist of structural officials, operational staff, and external partners like school leaders and education inspectors. The results indicate that conflicts can be functional or dysfunctional; functional conflicts encourage creativity in problem-solving, whereas dysfunctional ones obstruct cross-sector collaboration. Collaboration between units is successful on a technical basis but still lacks strength in the stages of planning and policy assessment. The conversation emphasizes that transformational leadership, transparent communication, and teamwork are vital for minimizing conflicts and improving coordination. In summary, the success of implementing regional priority programs in the Sidoarjo Education and Culture Office significantly relies on flexible conflict resolution and inter-sector cooperation founded on teamwork and openness.